Scientific Scepticism and Epistemic Justification: Revisiting the Higher Values of Contextualistic Pluralism - Etuk, Anthony Raphael; Ujoh, Emmanuel Amoji (NIU Journal of Humanities, 2023)
Scientific scepticism, fundamentally, questions the veracity and epistemic value of claims not supported by scientific evidence. Motivated by the assumption that only the empirical investigation of reality leads to the truth, the scientific sceptics maintain that only scientific method is best suited for this purpose. Claims found to be wanting in scientific evidence are considered untrue, and of little or no epistemic consequence. Using the analytical and critical methods, this paper interrogates this epistemic criterion of justification of scientific scepticism. It shows the inherent epistemic deficits in this criterion of the scientific sceptics, and how absolutizing its demands in such a manner as to undermine the veracity and epistemic significance of claims outside the mainstream discipline of science is not only to entrap themselves in many epistemic burdens, but to sink under the weight of criteriological egocentrism, detrimental to cognitive progress. As a credible alternative, this paper explores the epistemic fecundity of contextualistic pluralism – the pluralism of contextually underwritten cognitive positions – in case of truth and knowledge justification. It concludes with emphasis on the relevance of this approach to epistemic justification in our age of interculturality, by shifting the focus of philosophical thinking from identity to diversity. Keywords: Scientific, Scepticism, Knowledge, Contextualistic Pluralism, Truth, Empirical.